Discursive methods and the cross-linguistic study of ASD: a conversation analysis case study of repetitive language in a Malay-speaking child - Mohamed Zain, Nor Azrita; Muskett, Tom; Gardner, Hilary (Palgrave Macmillan Publishers, 2017)
In this chapter Mohamed Zain and colleagues provide an account of formulaic and repetitive language produced by a preschool-aged Malay-speaking child with mild ASD. Using conversation analysis (CA), they consider the functions of a repetitive expression, ‘apa tu’ (‘what’s that’), that was used frequently by the child across two 30-minute dyadic play sessions. By positioning the analyses against existing ASD-relevant findings about interactions involving English-speaking participants, the authors reflect upon the possibilities offered by CA for cross-linguistic research about diagnosed individuals.